ECOSYSTEM MANAGEMENT AND IMPACT OF JATIGEDE RESERVOIR CONSTRUCTION ACTIVITIES IN THE POLITICAL ECOLOGY PERSPECTIVE - Haryanti, Rinrin; Kurniawan, Kunkun Kobul (Progress In Social Development, 2025)
Jatigede Reservoir construction activities in Sumedang Regency have an impact on various aspects. The purpose of this research is to reveal the impact of Jatigeda reservoir development on ecological and community socio-economic aspects. The research method is descriptive with a qualitative approach through observation and in-depth interviews. The results of the research show that significant changes occurred in the conversion of agricultural land and settlements to stagnant water flows. Meanwhile, changes in society lives have been identified as changes in livelihoods, shifts in living habits and cultural customs, as well as psychological impacts. This especially happens to directly affected communities. So that management can be carried out through a political ecology perspective approach, namely with an integrated collaborative pattern between the central government, regional governments and affected communities. The political ecology approach used in this research focuses on environmental political aspects with ecological and social impacts.